Intra- and post-operative acute hemorrhagic complications of Onyx embolization of brain arteriovenous malformations: A single-center experience - Chen, Xuan; Wang, Yiheng; Yu, Jinlu (Frontiers in Neurology, 2022)
Background The intra- and post-operative acute (within 72 h) hemorrhagic complications of endovascular treatment (EVT) for a brain arteriovenous malformation (BAVM) are disastrous. Thus, further experiential summaries are required to fully understand them. Materials and methods This was a retrospective study of 25 patients with consecutive BAVM who were treated via EVT with Onyx embolization and suffered intra- and post-operative acute hemorrhage. The clinical and imaging data of the patients were recorded, analyzed, and discussed. Result Twenty-five patients were aged 11–70 years (mean, 37.2 ± 16.1 years), of whom 12 were female (48%, 12/25). Of the 25 hemorrhagic complications, 17 (68%, 17/25) were intraoperative, and 8 (32%, 8/25) were post-operative and occurred between 1 and 12 h after EVT. Of 17 intraoperative hemorrhages, 13 (76.5%, 13/17) were due to high-pressure Onyx casting. Of eight post-operative hemorrhages, six (75%, 6/8) were attributed to normal perfusion pressure breakthrough. The degree of nidus Onyx embolization was more than 2/3 or complete in seven (87.5%, 7/8) BAVMs. Draining vein occlusion was observed in eight (32%, 8/25) of 25 BAVMs. After hemorrhage, conservative treatment was administered in 12 (48%, 12/25) cases, and surgical management was performed in other cases. There were eight cases of mortality; the remaining 17 patients had follow-up data. Among them, 15 patients had good outcomes, with Glasgow Outcome Scale scores of 5 and 4, accounting for 60% (15/25). Conclusion In EVT for BAVMs, intra- and post-operative acute hemorrhagic complications are disastrous; only 60% of patients have a good outcome. Therefore, high-pressure Onyx casting or casting too much Onyx at one time to pursue a high degree of nidus embolization should be performed cautiously, and primary draining vein occlusion should be avoided. In short, EVT needs to be performed carefully.